THEORETICAL FOUNDATIONS OF TEACHING FINE AND APPLIED ARTS BASED ON NATIONAL VALUES - Bozorova, Rukhshona (International Conference on Science, Education & Law, 2025)
This article explores the theoretical foundations of teaching fine and applied arts based on national values. It analyzes the integration of national heritage, customs, traditional art schools, and folk art into the educational process, as well as their significance in developing students’ aesthetic taste, artistic thinking, and creative competencies.